Systematic review of empowering Intangible Cultural Heritage with metaverse technology - Tan, Qian; Kamarudin, Khairul Manami; Herman, Siti Sarah (Association for Computing Machinery, 2025)
The metaverse is a virtual society capable of mapping the real world, bringing new opportunities and innovations for the transmission and development of Intangible Cultural Heritage (ICH). However, nowadays, the research on metaverse technology in the field of ICH needs to be more cohesive. Therefore, a comprehensive systematic review was conducted through an extensive search of ICH and metaverse-related technologies. The scope of the search is based on the studies from January 2019 to September 2023 of the three major databases of Web of Science, IEEE Xplore, and Scopus covering the keyword. This article provides a general overview of the use of metaverse technologies in ICH and its categories over 5 years. It explains the characteristics, features, and scope of varying metaverse technologies applied to different ICHs in detail. It also explores the prospects of using metaverse to empower ICH and finally discusses the effectiveness of using metaverse technologies to empower ICH and presents the current resistance. In this way, it provides a new direction for the ICH in meeting and integrating into the new era of the metaverse.